Panax Ginseng for Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-Analysis - Hassan , Husna; Mohd Noor , Noor Hayati; Draman, Nani; Badrin , Salziyan (IIUM Medical Journal Malaysia, 2025)
INTRODUCTION: Panax ginseng is a traditional Chinese medicine used for chronic obstructive pulmonary disease (COPD). The study assessed Panax ginseng’s advantages for patients with COPD. MATERIAL AND METHOD: PRISMA guidelines were used based on the PICOS model. A systematic search of PubMed/Medline and the Cochrane Library was conducted till March 2022. I2 statistic and random effects model was employed to assess heterogeneity, and GRADE assessment was used to evaluate the quality of outcomes. RESULTS: Four trials involving 469 participants were included. Panax ginseng had no significant effects in reducing the frequency of COPD exacerbations (p=0.08) or improve FEV1 (p=0.22), FEV1 (p=0.28), FVC (p=0.20), FVC (p=0.79), and FEV1/FVC ratio (p=0.06) as compared to the placebo. No effects on the mental health-related quality of life (p=0.94), physical health-related quality of life (p=0.92), and respiratory health-related quality of life (p=0.29) were observed. The severity of COPD (p=0.64) was also not affected. Adverse effects documented by Panax ginseng, including insomnia (p=0.15), epistaxis (p=0.69), respiratory tract infection (p=0.83), and white blood cells (p=0.33), were insignificant compared with placebo. CONCLUSIONS: There is low to moderate certainty of evidence that Panax ginseng improves exacerbation or lung functions in COPD patients. Thus, more high[1]quality double-blind RCTs are required to establish its clinical effectiveness, and at present, Panax ginseng should not be considered a substitute for conventional COPD treatment.